Hubungan Kepemimpinan Transformasional Kepala Sekolah dan Manajemen Berbasis Sekolah dengan Produktivitas Sekolah di SMA Negeri 1 Kramatwatu Kabupaten Serang - Lestari, Fitri Sekar; Sudadio, Sudadio (Universitas Mathla'ul Anwar Banten, 2023)
This research was conducted to determine the relationship between principal transformational leadership and school-based management with school productivity at SMA Negeri 1 Kramatwatu, Serang Regency. This research was carried by field research and method of correlation survey. The population in this study were all the teachers in SMA Negeri 1 Kramatwatu which in total 48 people. The sample were taken by saturation sampling which is obtained by the population number. The findings indicated that there is a positive relationship between principal transformational leadership and school-based management with school productivity. At the significance level α = 0,05 with n = 48 obtained a value t_table 1,684, so the results of transformational leadership test with t_count 12,517 > t_ table 1,684, showed a positive relationship between principal transformational leadership with school productivity. School-based management with t_count 12,626 > t_table 1,684, showed a positive relationship between school-based management with school productivity. The results of multiple correlation test F_count showed 89,073, so F_count 89.073 > F_table 3,200. It can be concluded that there is a positive relationship between principal transformational leadership and school-based management with school productivity at SMA Negeri 1 Kramatwatu, Serang Regency by 89,3%, and the remaining 10,7% were affected by other variables.